 # For each of the following functions, evaluate this expression. <math xmlns="http://www.w3.org/1998/Math/MathML"> <mfrac> <mrow> <mi>f</mi> <mo stretchy="false">(</mo> <mi>x</mi> <mo>+</mo> <mi>h</mi> <mo stretchy="false">)</mo> <mo>&#x2212;<!-- − --></mo> <mi>f</mi> <mo stretchy="false">(</mo> <mi>x</mi> <mo stretchy="false">)</mo> </mrow> <mi>h</mi> </mfrac> [/itex] Baladdaa9 2022-07-31 Answered
For each of the following function, evaluate this expression
$\frac{f\left(x+h\right)-f\left(x\right)}{h}$
1. $f\left(x\right)={x}^{2}-4x+5$
2. $g\left(x\right)={x}^{3}-2x+3$
3. $h\left(x\right)=\frac{1}{2x}$
You can still ask an expert for help

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it akademiks1989rz
Step 1
1) $\frac{f\left(x+h\right)-f\left(x\right)}{h}=\frac{\left(x+h{\right)}^{2}-4\left(x+h\right)+5-\left({x}^{2}-4x+5\right)}{h}$
$=\frac{\text{⧸}{x}^{2}+2xh+{h}^{2}-\text{⧸}4x-4h+\text{⧸}5-\text{⧸}{x}^{2}+\text{⧸}4x-\text{⧸}5}{h}$
$=\frac{h\left(2x+h-4\right)}{h}=2x+h-4$
Step 2
2) $\frac{g\left(x+h\right)-g\left(x\right)}{h}=\frac{\left(x+h{\right)}^{3}-2\left(x+h\right)+3-\left({x}^{3}-2x+3\right)}{h}$
$=\frac{{x}^{3}+3{x}^{2}h+3x{h}^{2}+{h}^{3}-2x-2h+3-{x}^{3}+2x-3}{h}$
$=\frac{h\left(3{x}^{2}+3xh+{h}^{2}-2\right)}{h}$
$=3{x}^{2}+3xh+{h}^{2}-2$
Step 3
3) $\frac{h\left(x+h\right)-h\left(x\right)}{h}=\frac{\frac{1}{2\left(x+h\right)}-\frac{1}{2x}}{h}$
$=\frac{2x-2\left(x+h\right)}{4xh\left(x+h\right)}$
$=\frac{-2h}{4xh\left(x+h\right)}=\frac{-1}{2x\left(x+h\right)}$